(untitled) (Journal of Contemporary Educational Policies and Practices, 2025)
This practical action research study reports how the doctoral-level Qualitative Research Methodology course offered by a Vietnamese university evolved over four years. Since the students were quantitatively oriented and of mixed disciplinary backgrounds, they struggled with the course immensely. In particular, they were highly skeptical of the qualitative research methodology. By assigning more discipline-appropriate reading materials and changing the material assignment mechanism over four intervention cycles, the students responded increasingly positively to the course and gradually overcame their prejudice against it. In addition, popular press books seemed to create a meaningful common space between the students and the instructor. While the interventions brought about more positive student learning experiences, the instructor found them painful, and some students remained skeptical of the course. This study is useful for those professors who teach research methods courses in Ph.D. programs, especially when the students struggle with the courses.